Refocusing Perspectives on Public Corruption Away from the Individual: Insights from the Moldovan Social Matrix - Alexandru Vasile ROMAN (Transylvanian Review of Administrative Sciences, 2014)
Public corruption has received significant attention from scholars across a large array of disciplines. Despite the numerous academic efforts, however, our current understandings of the motivation and the evolution of public corruption still suffer from an agonizing amount of ambiguity, and on many occasions fail to provide practical guidance. One of the reasons for the limited progress in the area is the fact that, given its nature, corruption does not lend itself easily to empirical studies. Especially rare is qualitative research that examines and challenges the findings of previous studies within different institutional, cultural and social environments. This article provides the results of a study that examined nine theory building propositions suggested by de Graaf and Huberts (2008) within the context of developing democracies, specifically the Republic of Moldova. The study confirmed six of the nine propositions. Among others, it was determined that in developing de- mocracies corruption is highly influenced by the social matrix and public officials often assume their positions with the implicit expectations of reaping rewards from corrupt behaviors.